A Novel Phenotype of Germline Pathogenic Variants in MAX: Concurrence of Pheochromocytoma and Ganglioneuroma in a Chinese Family and Literature Review - Chang, Xiaoyan; Li, Zelin; Ma, Xiaosen; Cui, Yunying; Chen, Shuchun; Tong, Anli (Frontiers in Endocrinology, 2020)
Background: MYC associated factor X (MAX) is a tumor suppressor gene, had been identified as one of the pathogenic genes of hereditary pheochromocytoma (PCC). To date, there have been no reports of ganglioneuroma (GN) with MAX variants. Case presentation: The proband was a 45-year-old Chinese female with paroxysmal hypertension and palpitations who had undergone adrenalectomy for PCC 14 years ago. Her plasma free normetanephrine and 24-hour urinary norepinephrine excretion were significantly increased, abdominal computed tomography (CT) revealed an irregular mass in the left adrenal region, suggesting a recurrence of PCC. The mass was surgically removed and pathologically diagnosed as PCC with lymph node metastasis. The proband's son suffered from paroxysmal hypertension and palpitations. His plasma free metanephrines levels were normal. CT revealed a mass in the right adrenal. The tumor was surgically removed and the pathological diagnosis was GN. Genetic testing of peripheral blood DNA revealed that the proband and her son had germline pathogenic MAX variants c. C97T, p.Arg33Ter, while proband’ parents did not have MAX variants. Tumor DNA sequencing showed the same MAX variants (c. C97T, p. Arg33Ter) in PCC of the proband and GN of her son, both with retention of heterozygosity. Immunohistochemistry demonstrated loss of MAX protein expression in most tumor cells in PCC of the proband and some Schwannian cells in GN of the proband’ son. Conclusion: We report a family with a new clinical phenotype of germline pathogenic variants in MAX who developed both PCC and GN. Germline pathogenic variants in MAX may contribute to the development of GN. Our findings suggest that it is not just paternally inherited MAX variants can cause tumors.